La retroalimentación en el aprendizaje significativo en estudiantes del área de ciencias sociales del primer grado de educación secundaria de la Institución Educativa Túpac Amaru, Iquitos 2023 - Muñoz Vasquez, Juleisy Cristina (2024)
The central task of this research was to determine the relationship between feedback and meaningful learning in students in Social Sciences at the secondary level. The research was correlational, opting for a quantitative design to collect data. The study population included 122 students and census sampling was used, considering the entire population as the sample. To collect information on the work variables, the questionnaire is used as an instrument. The most significant results show that with an error level of 0.0%, there is a very strong classification between the study variables. Consequently, the research hypothesis is confirmed, indicating that there is a statistically significant relationship with significant learning in students in Social Sciences in the first grade of secondary education at the Túpac Amaru Educational Institution Iquitos 2023.